Cirurgia estética para remoção de hiperplasia gengiva: granuloma piogênico - Scardueli, Cássio Rocha [UNESP]; Basso, Túlio Luiz Durigan [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Andrade, Cleverton Roberto de [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (My University, 2013)
The pyogenic granuloma, a lesion considered hyperplastic regenerative inflammatory reaction is a finding commonly found in the oral cavity, affecting large numbers of individuals, being more prevalent in females. But its pathogenesis is not well defined and may be associated with numerous factors that stimulate tissue proliferation. Correct diagnosis and treatment plan are essential for success in approach, restoring function and aesthetics to the periodontal tissues. In agreement with the literature, the most common treatment and greater predictability is surgical removal, which involves resection of the lesion, together with its base inserted into the underlying tissue, periosteum and bone tissue. However, the excision can promote aesthetic defects, particularly in anterior regions where it is most affected. This article reports on the importance of a correct surgical approach for removal of pyogenic granuloma in the region of the interdental papilla between teeth 42 and 43, resulting in a good anatomical result and aesthetic.

O granuloma piogênico, considerado como uma lesão hiperplásica reacional inflamatória regenerativa, é um achado comumente encontrado na cavidade oral, afetando grande número de indivíduos, sendo mais prevalente no sexo feminino. Porém, sua patogênese ainda não está bem definida, podendo estar associada a inúmeros fatores que estimulam a proliferação tecidual. O correto diagnóstico e o plano de tratamento são essenciais para o sucesso na abordagem, devolvendo a função e a estética aos tecidos periodontais. De consenso com a literatura, o tratamento mais usual e com maior previsibilidade é a remoção cirúrgica, que envolve a ressecção total da lesão, juntamente com sua base inserida no tecido subjacente, periósteo e tecido ósseo. No entanto, a excisão pode promover defeitos estéticos, principalmente em regiões anteriores, onde é mais acometido. Este artigo relatou a importância de uma correta abordagem cirúrgica para remoção de granuloma piogênico em região de papila interdental entre os dentes 42 e 43, resultando em um bom resultado anatômico e estético.
Esthetic surgery for removal gingival hyperplasia: pyogenic granuloma. Clinical case report
Keywords: Granuloma pyogenic; Gingival hyperplasia; Diagnosis oral; Surgery oral; Granuloma piogênico; Hiperplasia gengival; Diagnóstico Bucal; Cirurgia Bucal